(untitled) (Boston, 2008)
This Thirty-Fifth Edition of ANNUAL EDITIONS: EDUCATION provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and an instructor’s resource guide with testing materials. USING ANNUAL EDITIONS IN THE CLASSROOM is offered as a practical guide for instructors.
Keywords: Education,Giáo dục